How to teach sustainable tourism development: The ICT4STD project - Stokłosa, Łukasz; Szpara, Krzysztof; Wójcik, Joanna (Turyzm/Tourism, 2022)
Sustainable tourism development and digital transformations are among the key issues that should be taken into account when preparing contemporary tourism degree programmes. In order to offer an innovative curriculum, systems thinking and knowledge from the intersection of many areas including tourism, geography, information and communication technology, management, teaching methodology and psychology are required. The adaptation of curricula should also take into account the experience of universities outside Poland which have often successfully implemented programmes covering sustainable development issues for many years and have feedback on the satisfaction of both graduates and employers. This article presents the results of the work of an international consortium of universities from Germany, Poland, Serbia and Switzerland which developed a course programme on ‘ICT as a tool for the development and promotion of sustainable tourism’ that can be adapted by a wide range of organisations such as universities, NGOs and tourism training companies.